I am choosing an integer. I then subtract 10 from the integer, take the opposite of the result, add -3, and find the opposite of the new result. My result is - 3. a) What is the original number? b) Judy wants to do the activity with her classmates. Each classmate probably chooses a different number and Judy wants to tell each classmate quickly what number was chosen. Judy figures out that the only thing she needs to do is to add 7 to each answer she gets. Does this always work? Explain why or why not. The original number is Will adding 7 to each answer always result in the original number? Explain. OA. Yes, let x be the number and a be the answer. Then the following is true. -[-(x+10) +- 3] = a -[-x+10+ -3] = a -(-x+ 7) = a x+ -7 = a x = a +7 OB. No, let x be the number and a be the answer. Then the following is true. -[-(x+10)+ - 3] = a -[-x+10+3] = a -(-x+13)=a x+13=a x=a + 13
I am choosing an integer. I then subtract 10 from the integer, take the opposite of the result, add -3, and find the opposite of the new result. My result is - 3. a) What is the original number? b) Judy wants to do the activity with her classmates. Each classmate probably chooses a different number and Judy wants to tell each classmate quickly what number was chosen. Judy figures out that the only thing she needs to do is to add 7 to each answer she gets. Does this always work? Explain why or why not. The original number is Will adding 7 to each answer always result in the original number? Explain. OA. Yes, let x be the number and a be the answer. Then the following is true. -[-(x+10) +- 3] = a -[-x+10+ -3] = a -(-x+ 7) = a x+ -7 = a x = a +7 OB. No, let x be the number and a be the answer. Then the following is true. -[-(x+10)+ - 3] = a -[-x+10+3] = a -(-x+13)=a x+13=a x=a + 13
Algebra and Trigonometry (6th Edition)
6th Edition
ISBN:9780134463216
Author:Robert F. Blitzer
Publisher:Robert F. Blitzer
ChapterP: Prerequisites: Fundamental Concepts Of Algebra
Section: Chapter Questions
Problem 1MCCP: In Exercises 1-25, simplify the given expression or perform the indicated operation (and simplify,...
Related questions
Question
![I am choosing an integer. I then subtract 10 from the integer, take the opposite of the result, add -3, and find the opposite of the new result. My result is - 3.
a) What is the original number?
b) Judy wants to do the activity with her classmates. Each classmate probably chooses a
different number and Judy wants to tell each classmate quickly what number was chosen.
Judy figures out that the only thing she needs to do is to add 7 to each answer she gets.
Does this always work? Explain why or why not.
The original number is
Will adding 7 to each answer always result in the original number? Explain.
O A. Yes, let x be the number and a be the answer. Then the following is true.
-[-(x + −10) + −3] = a
-[-x+ 10 + −3] = a
-(-x + 7) = a
x +
7 = a
x = a +7
B. No, let x be the number and a be the answer. Then the following is true.
-[-(x+10)+ - 3] = a
-[-x + 10 +3] = a
-(-x+13) = a
x+13=a
x = a + 13](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2Fc93bf6ec-99c8-413d-8186-260b6c8bf86c%2Fb33a4e45-898f-46cc-aba2-fbfe7878dc54%2Fj9w3ubk_processed.png&w=3840&q=75)
Transcribed Image Text:I am choosing an integer. I then subtract 10 from the integer, take the opposite of the result, add -3, and find the opposite of the new result. My result is - 3.
a) What is the original number?
b) Judy wants to do the activity with her classmates. Each classmate probably chooses a
different number and Judy wants to tell each classmate quickly what number was chosen.
Judy figures out that the only thing she needs to do is to add 7 to each answer she gets.
Does this always work? Explain why or why not.
The original number is
Will adding 7 to each answer always result in the original number? Explain.
O A. Yes, let x be the number and a be the answer. Then the following is true.
-[-(x + −10) + −3] = a
-[-x+ 10 + −3] = a
-(-x + 7) = a
x +
7 = a
x = a +7
B. No, let x be the number and a be the answer. Then the following is true.
-[-(x+10)+ - 3] = a
-[-x + 10 +3] = a
-(-x+13) = a
x+13=a
x = a + 13
Expert Solution

This question has been solved!
Explore an expertly crafted, step-by-step solution for a thorough understanding of key concepts.
This is a popular solution!
Trending now
This is a popular solution!
Step by step
Solved in 3 steps

Recommended textbooks for you

Algebra and Trigonometry (6th Edition)
Algebra
ISBN:
9780134463216
Author:
Robert F. Blitzer
Publisher:
PEARSON

Contemporary Abstract Algebra
Algebra
ISBN:
9781305657960
Author:
Joseph Gallian
Publisher:
Cengage Learning

Linear Algebra: A Modern Introduction
Algebra
ISBN:
9781285463247
Author:
David Poole
Publisher:
Cengage Learning

Algebra and Trigonometry (6th Edition)
Algebra
ISBN:
9780134463216
Author:
Robert F. Blitzer
Publisher:
PEARSON

Contemporary Abstract Algebra
Algebra
ISBN:
9781305657960
Author:
Joseph Gallian
Publisher:
Cengage Learning

Linear Algebra: A Modern Introduction
Algebra
ISBN:
9781285463247
Author:
David Poole
Publisher:
Cengage Learning

Algebra And Trigonometry (11th Edition)
Algebra
ISBN:
9780135163078
Author:
Michael Sullivan
Publisher:
PEARSON

Introduction to Linear Algebra, Fifth Edition
Algebra
ISBN:
9780980232776
Author:
Gilbert Strang
Publisher:
Wellesley-Cambridge Press

College Algebra (Collegiate Math)
Algebra
ISBN:
9780077836344
Author:
Julie Miller, Donna Gerken
Publisher:
McGraw-Hill Education